2016
DOI: 10.1016/j.bjane.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lidocaine and esmolol infusions on hemodynamic changes, analgesic requirement, and recovery in laparoscopic cholecystectomy operations

Abstract: In laparoscopic cholecystectomies, lidocaine infusion had superiorities over esmolol infusions regarding the suppression of responses to tracheal extubation and postoperative need for additional analgesic agents in the long run, while esmolol was more advantageous with respect to rapid recovery from anesthesia, attenuation of early postoperative pain, and modified Aldrete recovery (MAR) scores and time to reach MAR score of 9 points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…Similar to our findings, Dogan et al found no difference between the two groups in postoperative 24 hours opioid consumption after laparoscopic cholecystectomy. 16 In contrast, Kavak Akelma et al found significantly less fentanyl requirement in patients receiving esmolol than those receiving lidocaine infusion or placebo in the first 24 hours of surgery. 17 This difference might be due to the higher dose of esmolol (fixed dose, 50 µg/kg/min) used in their patients in comparison to ours (esmolol infusion limited to 15 µg/kg/min).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar to our findings, Dogan et al found no difference between the two groups in postoperative 24 hours opioid consumption after laparoscopic cholecystectomy. 16 In contrast, Kavak Akelma et al found significantly less fentanyl requirement in patients receiving esmolol than those receiving lidocaine infusion or placebo in the first 24 hours of surgery. 17 This difference might be due to the higher dose of esmolol (fixed dose, 50 µg/kg/min) used in their patients in comparison to ours (esmolol infusion limited to 15 µg/kg/min).…”
Section: Discussionmentioning
confidence: 92%
“…15 However, the significant difference in postoperative opioid consumption was limited to the PACU stay only (standard mean difference, −1.21; 95% CI, −1.66 to −0.77). Trials by Dogan et al 16 and Kavak et al 17 were not included, and perhaps inclusion of these studies might have further influenced the treatment effects. In a similar model to ours (laparoscopic cholecystectomy), 21 however, with a conventional control consisting of general anesthesia with opioids, the intraoperative fentanyl consumption was 200.5 µg in placebo group while it was null in esmolol group.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, the significant difference in postoperative opioid consumption was limited to the PACU stay only (standard mean difference, −1.21; 95% CI, −1.66 to −0.77; p ≤ 0.001). Trials by Dogan et al 16 and Kavak et al 17 were not included, and perhaps inclusion of these studies might have further influenced the treatment effects. In a similar model to ours (laparoscopic cholecystectomy), 21 however, with a conventional control consisting of general anesthesia with opioids, the intraoperative fentanyl consumption was 200.5 µg in placebo group while it was null in esmolol group.…”
Section: Discussionmentioning
confidence: 99%
“…However, single model analgesia is adequate for aged patients after surgery and multimodal analgesia is recommended to decrease postoperative pain intensity, opioid consumption and short length of hospital stay. Some published articles [13,[42][43][44] have shown that IV lidocaine reduced pain and shorten length of hospital stay, in addition, there was a lower inflammatory in IV lidocaine and lower risk of postoperative nausea and vomiting. Thus, IV lidocaine was more preferred to use in intraoperation and after surgery.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Nevertheless none of them has indicated identical efficacy and opioid medications can caused side effects including nausea and vomiting, megrim, constipation and delay of postoperative early recovery. Recently, some studies have revealed that perioperative continuous intravenous lidocaine infusion improved postoperative outcomes in postoperative pain, consumption of opioid medications and length of hospital stay (LOS) [13][14][15][16] . However, its effect on postoperative outcomes is not well identified due to their small sample and the deficiency of multicenter and large sample randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%